KELUARGA BERWAWASAN EKOLOGIS - Rumampuk, Selvie (Universitas Sam Ratulangi, 2019)
The family is the basic cell of society as the formation of religious values and culture to every human being on which different though, learning to live together with others and to belong to each other. The family also became the starting point for building a